Level of Student Cycle in Local Process (Survey Study In Physical Education Student of FKIP UNTAN Pontianak) - Viktor Simanjuntak; Januar Inggar Yadi (STKIP Singkawang, 2018)
The problem in this research is that in the lecture, there are always students who come late, even if they attend the lecture only to note their presence, in collecting the task given by the lecturer is always late from the set schedule, the lack of awareness of discipline and the sense of responsibility to carry out the order. The purpose of this research is to know the level of discipline, attitude, honesty and responsibility of physical education student FKIP UNTAN. The approach used in this research is descriptive method in the form of survey. The population is all students of Physical Education Program FKIP UNTAN odd semester of 186 people. The sample used a total sampling of 186 people.The results are classified into three classifications that are very good at 17.2%, both at 65.1% and enough at 17.7%. While the total score of grouping of attitude, honesty and overall responsibility level is 25301 which is included in the good classification, indicating that student discipline in lecturing process has been running well.